Historical Variations in the Catholic and Evangelical Image of Martin Luther - Madrigal, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
This article intends to study the creation, evolution and transmission of Luther’s images and counter-images. It’s focused on the confesional origins of the Reformer’s portrait: an authorized prophet of God to Protestants (Melanchton) and a devilish heresiarch for Catholic polemist (Cochläus). In the Catholic Luther Research occupies a special place the work of Joseph Lortz (Die Reformation in Deutschland, 1939-1940), with the postulate on the “Catholic Luther”. Historically, the Second Vatican Council signifies a certain turning point; substantivelly this new research is characterized by an astonishing and highly significant rapprochement to Luther wich can be described as the discovery of Martin Luther as a “Catholic possibility”. Peter Manns presented the cathegory of “father in the faith” (1Cor 4:15) as decisive for the disclosure of Luther’s ecumenical significance. New times to overcome barrieres and go from the conflict to the communion.
Keywords: Reform; Luther; images of Luther; confesional historiography; Lutheran-Catholic ecumenical dialogue; Joseph Lortz; Catholic Luther